Studi Empiris Determinan Nilai Perusahaan di Indonesia - Rifka Shaharudin; Abriyani Puspaningsih (Universitas Negeri Padang, 2022)
The aims of this study were to find some factors that effect to firm value. The objective of this study is to prove the indirect effect of Good Corporate Governance which is proporated by Audit Committee, Board Of Directors and Board Independen Commissioner. This study takes sample from 11 companies in the food and beverages sub sector at the Indonesia Stock Exchange, which were listed from 2013-2017. Sampling method in this study used purposive sampling. The method of analysis in this research used multiple regression. The results of this study show that audit committee, board Independen Commissioner, profitability, and firm growth had positive significant influence to firm value. Meanwhile, debt policy and board of directors had negative significant influence to firm value. Firm Size on the other hand had not significant influence to firm value. The contribution of this research is: Keywords: GCC, Debt Policy, Firm Size, Firm Value